Holographic Transport with Topological Term and Entropy Function - Nastase, Horatiu [UNESP]; Tiedt, Caio Luiz (Springer Nature, 2024)
In this paper, we consider the effect of a topological Maxwell term W(Φ)FμνF~μν on holographic transport and thermodynamics in 2 + 1 dimensions, in the case with a dyonic black hole in the gravity dual. We find that for a constant W the modifications to the thermodynamics are easily quantified, and transport is affected only for σxy. If one considers also the attractor mechanism, and writing the horizon transport in terms of charges, the transport coefficients are affected explicitly. We also introduce the case of radially dependent W(z), in which case, however, analytical calculations become very involved. We also consider the implications of the two models for the S-duality of holographic transport coefficients.